2018
DOI: 10.1021/acsenergylett.8b00009
|View full text |Cite
|
Sign up to set email alerts
|

Water-in-Salt Electrolyte for Potassium-Ion Batteries

Abstract: Concentrated potassium acetate as a water-in-salt electrolyte provides a wide potential window from −1.7 to 1.5 V vs Ag/AgCl KCl sat. . It facilitates the reversible operation of KTi 2 (PO 4 ) 3 , an anode of potassium-ion batteries, that otherwise only functions in nonaqueous electrolytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
230
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(233 citation statements)
references
References 14 publications
0
230
0
3
Order By: Relevance
“…When coupled with Zn anode, the battery shows impressive 1.9 V open‐circuit voltage, and 142 mAh g −1 at 3 C (416 mA g −1 ). Recently, a “water‐in‐salt” electrolyte of concentrated potassium acetate (KAc) solution was utilized by Ji and co‐workers to extend electrochemical window for AKIBs . In virtue of the wide electrochemical window (from −1.7 to 1.5 V vs Ag/AgCl), KTi 2 (PO 4 ) 3 (KTP, only feasible in nonaqueous electrolyte previously) can be evaluated as anode in 30 m KAc, and it can deliver 53 mAh g −1 specific capacity .…”
Section: Aqueous Rechargeable Batteries Using Monovalent Ions (Li+ Nmentioning
confidence: 99%
“…When coupled with Zn anode, the battery shows impressive 1.9 V open‐circuit voltage, and 142 mAh g −1 at 3 C (416 mA g −1 ). Recently, a “water‐in‐salt” electrolyte of concentrated potassium acetate (KAc) solution was utilized by Ji and co‐workers to extend electrochemical window for AKIBs . In virtue of the wide electrochemical window (from −1.7 to 1.5 V vs Ag/AgCl), KTi 2 (PO 4 ) 3 (KTP, only feasible in nonaqueous electrolyte previously) can be evaluated as anode in 30 m KAc, and it can deliver 53 mAh g −1 specific capacity .…”
Section: Aqueous Rechargeable Batteries Using Monovalent Ions (Li+ Nmentioning
confidence: 99%
“…[81] Since the ratio of water to the lithium salt is smaller than unity, the electrolyte is considered as a water-in-salt in lieu of saltin-water (similar to the terminology quoted in Section 2.2). Albeit, the idea of water-in-salt has been used for the fabrication of supercapacitors [88,89] sodium-ion batteries (SIBs), [85,90,91] and potassium-ion batteries (KIBs) [92] too. Unfortunately, this brilliant approach has not appropriately attracted the attention of researchers in the field, and the majority of available papers are still by the same research group.…”
Section: Water-in-saltmentioning
confidence: 99%
“…[89,92] The key feature of this novel class of ARLB electrolytes is the capability of forming a protective SEI on the electrode surface, which can defer the evolution reactions. The stable potential window widens by the molality of the salt.…”
Section: Water-in-saltmentioning
confidence: 99%
“…Further, this combination of aqueous KIB could achieve an energy density of 80 Wh kg −1 with a good rate capability (20C) and wide temperature range of −20 to 60 °C . A study conducted by Ji et al, utilized KTi 2 (PO 4 ) 3 as anode and potassium‐acetate‐based aqueous solution as electrolytes . This study reported a working voltage window of 3.2 V (−1.7 to 1.5 V vs Ag/AgCl KCl sat ) for aqueous KIBs, which is considered to be very high operating voltage window for aqueous KIBs.…”
Section: Different Electrolytesmentioning
confidence: 99%
“…The aqueous electrolyte‐based KIBs are considered to be a potential candidate for the grid‐scale applications mainly due to its non‐flammable nature . Other advantages of using aqueous batteries are its low cost, sustainability, environmental friendly nature, stability in air, ability to withstand overcharge due to the oxygen cycle, high electrolyte conductivity, etc.…”
Section: Different Electrolytesmentioning
confidence: 99%